(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Metabolic syndrome is defined as a constellation of interconnected physiological, biochemical, clinical and metabolic factors that directly increase the risk of cardiovascular disease and Type 2 Diabetes Mellitus. It is a major and increasing public health problem and clinical challenge worldwide in the wake of urbanization, increasing obesity and sedentary life style. Metabolic syndrome defined by IDF (2006) as presence of Central obesity with any one of the 3 factor i.e., Raise Triglyceride, Reduced HDL, Raised BP or Raised FBS. It increases 5 fold risk of Type II DM and 2 fold risk of Cardio-vascular disease. Worldwide prevalence of Metabolic syndrome ranges from 10% to 84% depending upon the Region (Urban/Rural), Composition (sex, age, race, ethnicity) of Population. IDF estimates that 1/3rd of world Adult population have Metabolic Syndrome. According to NCEP - ATP III CRITERIA 2001 Metabolic syndrome varies from 8 to 43% in men and 7 to 56% in women around the world. Lifestyle modification remains the initial intervention of choice as majority of people have sedentary lifestyle high socio economic status high BMI and are overweight. So lifestyle modification combine with specific Ayurvedic therapies i.e., Palliative (Shaman), Panchkarma (Shodhan), Sadhvrit (good conduct/ethical regimen for balanced state), Exercise and Diet, Yogic Practices etc. could be effective in the Management of Metabolic Syndrome.